Penguatan Kompetensi Kerja Industri Perhotelan melalui Pelatihan Pelayanan Restoran di Hotel Bina Darma Palembang (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This training activity aims to strengthen the work competency of vocational students in the hospitality industry, particularly in the restaurant service aspect. The training was held on May 23, 2025, at the Bina Darma Hotel, Palembang, involving students from the Hospitality and Culinary Arts Study Program at the Prasetiya Mandiri Polytechnic, Palembang. The methods used were experiential learning and industry-based training, which emphasize learning through direct experience in a real work environment and reflection on the practices carried out. During the training, students were actively involved in restaurant service activities, from welcoming guests and serving food and drinks, to implementing work ethics and professional communication. Evaluation results showed a significant improvement in the students' service skills, communication skills, and work attitudes. In addition to providing benefits to the students, this activity also provides benefits to the hotel in the form of additional staff support in service and potential long-term collaborations. Overall, this training is in line with the Merdeka Belajar-Kampus Merdeka (MBKM) policy that encourages project-based learning and industry partnerships, and has proven effective in increasing employability skills and strengthening the synergy between the world of vocational education and the world of work.